A Tumor-Like Lump in the Palm Caused by an Inconspicuous-for 75 Years-Bullet - Efstratios D. Athanaselis; Apostolos Fyllos; Nikolaos Stefanou; Socrates E. Varitimidis; Dimitrios Giannikas (Case Reports in Orthopedics)
Case. An unusual case of a foreign body in the hand is described here. Excision of a tumor-like soft tissue mass revealed a 75-year-old World War II bullet fragment of which patient was unaware. Conclusion. Differential diagnosis of hand lumps and inflammatory reaction must always include retained foreign bodies even after a very long period of posttraumatic quiescence or patient’s inability to provide a relative injury case history.